Surface plastic deformation study of directionally solidified nickel-based superalloy machined by ultrasonic vibration grinding - Pingzhong Zhu; Feifei Cai; Zhigang Dong; Nianwei Xu; Renke Kang; Wei Han; Yuan Zhang (Journal of Materials Research and Technology, 2025)
Directionally solidified nickel-based superalloy exhibits anisotropic mechanical properties attributed to the removal of detrimental transverse grain boundaries. This inherent anisotropy gives rise to intricate plastic deformation behaviors of the machined surface material during the grinding process. This study focuses on the formation process of plastic deformation in the ground surface of the directionally solidified nickel-based superalloy. A comprehensive comparison is conducted on the plastic deformation mechanism of ground surface between conventional grinding and ultrasonic vibration grinding. The findings indicate that, among different machining orientations, the longitudinally ground surface shows the maximum depth of plastic deformation and work hardening, while the transversely ground surface exhibits the minimum. Notably, ultrasonic vibration grinding significantly exacerbates plastic deformation and work hardening of ground surface. This result can be attributed to the additional plastic deformation induced by ultrasonic vibrations in the normal direction. This research not only clarifies the unique grinding-induced plastic deformation characteristics of directionally solidified nickel-based superalloy but also reveals the underlying plastic deformation mechanism of ultrasonic vibration grinding. The findings of this study can provide valuable references for optimizing the grinding processes of turbine blades made from this special alloy.